Recurrent Subcutaneous Phaeohyphomycosis with Bone Involvement after Kidney Transplant - Sandhya Suresh; P. R. Appan Prakash; Ramprasad Elumalai; Jayakumar Matcha; Manikantan Shekar; Barathi Gunabooshanam (Indian Journal of Transplantation, 2025)
Phaeohyphomycosis is the term used to describe infections due to dematiaceous fungi which can cause cutaneous, pulmonary, and sinus infection, especially in immunocompromised patients. A 32-year-old deceased donor renal transplant recipient presented 8 months posttransplant with subcutaneous nodule in the epigastric region. Biopsy showed pigmented, septate hyphae and he received itraconazole for 2 months. Three years later, he noticed recurrence of nodule and multiple nodules in the right foot with a right leg ulcer. Magnetic resonance imaging of the right leg showed underlying bone involvement. He underwent excision of the lesions along with extensive surgical debridement for recurrent phaeohyphomycosis. Lesions persisted despite prolonged itraconazole therapy and reduction of immunosuppression. He also had acute graft dysfunction due to tacrolimus toxicity requiring dose reduction. This is an unusual case of phaeohyphomycosis highlighting the risk of recurrence and deep tissue involvement as well as the therapeutic challenges of this infection.